Mães psicóticas e seus bebês: uma leitura winnicottiana - Sérgio Luiz Saboya Arruda; Elisângela Andrieto (Arquivos Brasileiros de Psicologia, 2009)
Winnicott's theory emphasizes the relationship of the mother to her baby at the beginning and supports that mental health is related to child's primitive emotional development. Based on Winnicott's texts, it is discussed the early mother-infant relationship with emphasis on the emotional development of children whose mothers might have been affected by some psychotic disorder. Also the primary maternal preoccupation and the child¿s inherited tendency towards development are discussed.